PCR – Based Detection of Microcystin and Nodularin in both Freshwater and Bloom in Tigris River - Abed, Ibrahim J; Abdulhasan, Ghusoon A; Juyuan, Zhang; Han, Hu; Zhang, Shaoran; He, Qigai (Al-Nahrain Journal of Science, 2018)
Cyanobacterial blooms have a range of social, environmental and economic impacts due to their content of secondary metabolites involving toxins. Microcystins (MCs) is one of the cyanotoxins found in freshwater ecosystems. This study was aimed to adopt a rapid technique for determining the microcystin in blooms and freshwater by the detection of phycocyanin operon of cyanobacteria using PCβF and PCαR primers as well as mcyE gene encoding to microcystin/ nodularin using HEP primers. The molecular results showed that phycocyanin operon and mcyE gene were disclosed in the freshwater and bloom of samples at the studied sites. In conclusion, The PCR assay used in this study was helpful and rapid, in particular when the target organism concentration in the freshwater sample is very low.